Prevalence of cardiovascular symptoms in post-acute COVID-19 syndrome: a meta-analysis - Li-wei Huang; Hua-min Li; Bei He; Xiao-bo Wang; Qi-zhi Zhang; Wen-xing Peng (BMC Medicine)
Abstract Background Since its emergence in 2019, COVID-19 has continued to pose significant threats to both the physical and mental health of the global population, as well as to healthcare systems worldwide (Raman et al., Eur Heart J 43:1157–1172, 2022). Emerging evidence indicates that COVID-19 may lead to post-acute COVID-19 syndrome (PACS) with cardiovascular implications, potentially driven by factors such as ACE2 interaction with viruses, systemic inflammation, and endothelial dysfunction. However, there remains a limited amount of research on the cardiovascular manifestations of PACS, which may delay the development of optimal treatment strategies for affected patients. Therefore, it is crucial to investigate the prevalence of cardiovascular sequelae in COVID-19 patients and to determine whether COVID-19 infection acts as an independent risk factor for these outcomes. Methods This meta-analysis adhered to PRISMA guidelines and was registered in PROSPERO (CRD42024524290). A systematic search of PubMed, Embase, and the Cochrane Library was conducted up to March 17, 2024. The primary outcomes included hypertension, palpitations, and chest pain, with pooled effect estimate reported as proportions and odds ratios (ORs) with 95% confidence intervals (CIs). Sensitivity and subgroup analysis were performed to assess the robustness of the results and to identify sources of heterogeneity. Results A total of 37 studies, encompassing 2,965,467 patients, were included in the analysis. Pooled results from case–control studies revealed that, compared to the control group, the ORs of chest pain in the COVID-19 group was 4.0 (95% CI: 1.6, 10.0). The ORs for palpitation and hypertension were 3.4 (95% CI: 1.1, 10.2) and 1.7 (95% CI: 1.6, 1.8), respectively. The proportions of PACS patients experiencing chest pain, palpitation, and hypertension as sequelae were 22% (95% CI: 14%, 33%), 18% (95% CI: 13%, 24%), and 19% (95% CI: 12%, 31%), respectively. Conclusions Our findings indicate that 15% of COVID-19 patients experience cardiovascular sequelae. Furthermore, COVID-19 infection significantly increases the likelihood of developing these sequelae compared to uninfected individuals. Future research should prioritize investigating the underlying pathological mechanisms and developing targeted preventive and management strategies. Trial registration CRD42024524290.